Решение задач о свободных колебаниях конических оболочек переменной толщины - Григоренко, А.Я.; Мальцев, С.А. (Видавничий дім "Академперіодика" НАН України, 2009)
Наводиться чисельно-аналiтичний пiдхiд для дослiдження вiльних коливань тонких конiчних iзотропних оболонок змiнної товщини, який базується на сплайн-апроксимацiї невiдомих функцiй. Розрахунки виконанi для рiзних типiв граничних умов. Дослiджено вплив змiнної товщини на характер поведiнки динамiчних характеристик. The paper considers free vibrations of thin isotropic conical shells with variable thickness basing on the method of spline-approximation of unknown functions. Calculations were carried out for different types of boundary conditions. The influence of a variable thickness of shells on free vibrations is studied. Free vibrations of shells with constant and variable thicknesses are compared.